2013
DOI: 10.1016/j.jmaa.2012.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Absolutely continuous multilinear operators

Abstract: Abstract. We introduce the new class of the absolutely (p; p1, ..., pm; σ)-continuous multilinear operators, that is defined using a summability property that provides the multilinear version of the absolutely (p, σ)-continuous operators. We give an analogue of Pietsch's Domination Theorem and a multilinear version of the associated Factorization Theorem that holds for absolutely (p, σ)-continuous operators, obtaining in this way a rich factorization theory. We present also a tensor norm which represents this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…A series of recent works [6][7][8][28][29][30] on Pietsch Domination-Factorization Theorems have shown that the domination theorem actually needs almost no linear structure, and a quite general version is in fact valid (see Theorem 2.2 below). This general approach recovers several previous Pietsch-type domination theorems (see [8]) and also rapidly found applications in different contexts (see [1,11,13]). …”
Section: The Full General Pietsch Domination Theoremsupporting
confidence: 71%
“…A series of recent works [6][7][8][28][29][30] on Pietsch Domination-Factorization Theorems have shown that the domination theorem actually needs almost no linear structure, and a quite general version is in fact valid (see Theorem 2.2 below). This general approach recovers several previous Pietsch-type domination theorems (see [8]) and also rapidly found applications in different contexts (see [1,11,13]). …”
Section: The Full General Pietsch Domination Theoremsupporting
confidence: 71%
“…Then Theorem 3.7 when applied with these elements gives the factorization result that can be found in [5, Theorem 2.1.20] (see also [1] and [4]). …”
Section: Let Us Consider Now the Quotient Mapmentioning
confidence: 74%
“…Using classical methods it can be shown that g p,σ is a norm on X 1 ⊗ · · · ⊗ X m ⊗ X with the metric mapping property (see the proof of Proposition 4.1 and 4.2 in [10])…”
Section: 2] and [18 Proposition 42]) And The Results Is Obtained Bmentioning
confidence: 99%
“…A related concept and a new generalizations of the concept of Cohen strongly summing multilinear operators have also been recently studied in [8,7,2,3]). For more details concerning the nonlinear theory of summing operators and recent developments and applications we refer to [1,10].…”
Section: ])mentioning
confidence: 99%